Effectiveness Of Ovitrap Socialization On Increasing Knowledge About How To Control Dengue Fever (Dhf) In Students At Smp Darma Medan - Alvi Nur Ilmi; Nurul Indah Nasution; Siti Nur Aisyah; Meutia Nanda; Ni'matul Ulya Munthe (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
At the end of 2022 in North Sumatra, the number of dengue cases reached 8,541 cases. This figure has increased significantly from the previous year, namely in 2021, which was 2,932 cases. The death rate due to dengue fever has also increased, where at the end of 2021 the death rate was 16 people to 60 people at the end of 2022. One of the efforts to control Dengue Hemorrhagic Fever (DHF) is by increasing efforts to eradicate the vector that transmits DHF. Ovitrap is a way to break the life cycle of mosquitoes that cause DHF. The purpose of this study was to determine the effectiveness of the socialization of ovitrap making on the knowledge of participants (students) about how to control the population of mosquito vectors that cause Dengue Hemorrhagic Fever. The experimental method in the form of a single case pretest-posttest design was used as a method in this study. To measure the success of the activity, a Pre-Test and Post-Test will be distributed with a questionnaire instrument before and after the socialization. The results obtained were an increase in students' knowledge by 45% after the socialization, with an average value before socialization of 6.3 and after socialization increasing to 9.1. So that the Ngain score value was 0.77 and the Ngain Score (%) 77% was obtained, which means that the Socialization of Ovitrap Making has an effectiveness in increasing the knowledge of students at SMP Darma Medan. The conclusion in this study is that the socialization carried out has an effectiveness that is useful for increasing students' knowledge and awareness of how to control Dengue Hemorrhagic Fever (DHF). The researcher suggests that teachers and parties responsible for students continue to monitor the development of understanding of Dengue Hemorrhagic Fever.